PENGANGKATAN ADAT SAUDARA KAWIN DI NEGERI TULEHU KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH DALAM MENYELESAIKAN KONFLIK DALAM RUMAH TANGGA - Gazali Rahman (IAIN Ambon, 2017)
Marriage aims to build a harmonious household. However, marital conflict, between husband and wife often happens in society. Villagers Tulehu have one custom relating to the marriage of local indigenous communities, commonly called sister mating. Sister mating is a man who was appointed by custom from the family of the bride, and more preferably from distant relatives nasabnya, so it can strengthen ties with family. Appointment sister mating take place prior to the marriage. Sister mating duties and function to benefit sister mating. In addition to providing material assistance, wedding brother to seek a peaceful solution to the conflict housekeeping sister mating. The brothers married a role as peacemakers, or hakam in Islamic law. Keywords: custom, sister mating, marriage, conflict resolution, household